Triticale as an alternative to milling wheat: the case of the Western Cape Province, South Africa - Terblanche, Frederik (University of the Free State, 2017)
The decline in the profitability of milling wheat is amongst the challenges faced by wheat producers in South Africa. The decline in profitability is hampering the ability of wheat producers to remain financially viable, and as a result, many producers have shifted their production focus to alternatives, which are believed to be more profitable. Producers in the Western Cape Province are, however, not that fortunate with the resource endowments that limit their options. Additionally, no attention has been given to the financial viability of alternatives for wheat production in the Western Cape Province. Therefore, this study examined triticale as an alternative crop. The financial viability of triticale, as compared with milling wheat, was determined by using the Agricultural Products Requirements Optimising (APR_OPT) model, coupled with a budget analysis. Results from the APR_OPT model in the form of demand and successive prices were used as inputs in the budget analysis to determine the financial viability of triticale, compared with milling wheat. Although triticale reported a positive gross margin for the period under review, its financial viability compared with milling wheat will largely depend on the prices of maize and milling wheat, respectively.

Die afname in die winsgewendheid van meulkoring is een van die uitdagings wat Suid-Afrikaanse koringprodusente in die gesig staar. Die afname in winsgewendheid onderdruk die vermoë van koringprodusente om finansieel lewensvatbaar te wees en het veroorsaak dat vele produsente hul produksiefokus verskuif het na alternatiewe wat meer winsgewend geag word. Produsente in die Wes-Kaap Provinsie is egter nie so gelukkig om, gegewe die beskikbare hulpbronne wat beperkende effekte het, ook sodanige skuiwe te oorweeg nie. Verder is daar nog geen aandag geskenk aan die finansiële lewensvatbaarheid van alternatiewe vir koringproduksie in die Wes-Kaap Provinsie nie. Hierdie studie ondersoek daarom die finansiële lewensvatbaarheid van korog as ŉ alternatiewe gewas teenoor meulkoring, met gebruik van die “Agricultural Products Requirements Optimising” (APR_OPT) model, saam met ŉ begrotingsanalise. Resultate vanaf die APR_OPT model in die vorm van vraag en toepaslike pryse, is gebruik as insette in die begrotingsanalise om die finansiële lewensvatbaarheid van korog in vergelyking met koring te bepaal. Alhoewel korog gedurende die betrokke tydperk ŉ positiewe bruto marge getoon het, sal die finansiële lewensvatbaarheid daarvan teenoor meulkoring, grootliks afhang van die pryse van mielies en meulkoring onderskeidelik.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2017
Keywords: Triticale -- Field experiments; Triticale; Wheat -- Milling